Modelling of examinations of artery wall thickness changes - POWAŁOWSKI, Tadeusz; WÓJCIK, Janusz; TRAWIŃSKI, Zbigniew (Archives of Acoustics, 2007)
The developed solver of acoustic field was used for simulation of the artery wall thickness examination. It is capable of describing spatial and time-dependent distribution of an ultrasonic beam, that is emitted by a piezoelectric ring transducer and then backscattered on cylindrical surfaces of the walls in artery models. The electrical signal received corresponds closely with the actual RF signal that is obtained during measurements at the output of the ultrasonic VED apparatus. The theoretical model of the artery for creating the ultrasonic reflected echoes was used. The internal radius of the artery model was equal 3 mm for the diastolic pressure and 3.3 mm for the systolic pressure. The intima-media thickness (IMT) of the artery wall was changed from 0.48 mm to 0.44 mm respectively. The echoes-tracking solver based on the zero-crossing and correlation methods was used for detecting changes of the IMT.